Literature Review: The Positive Value of Pencak Silat in the Learning Process and Sports Practice - Iswana, Bayu; Wanto, Sugar; Fahritsani, Husni; Nurudin, Ahmad Alwi; Kuswanto, Cahniyo Wijaya (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study explores the positive values gained from the process of learning pencak silat and pencak silat training (formal and non-formal) in children aged 5 years to 25 years. Materials and Methods. The research method used is literature review or literature analysis. Data collection techniques using Google scholar and Publish Or Peris.8 with the keyword ‘pencak silat value’ against articles from 2010 to 2024. The data analysis technique used PRISMA / Preferred Reporting Items For Systematic Reviews And Meta-Analyses with 7 articles as the main subject. The seven articles were selected based on the relevance of research results that have similarities in the learning process and pencak silat training in producing positive values (including character, spiritual, discipline, responsibility, religion, intellectual intelligence). Results. The results showed that pencak silat can instil the values of discipline, responsibility, morals and religion in early childhood obtained from the learning process. In addition, the pencak silat training process can form character values, spirituality, love for the country, emotional intelligence, brotherhood and can reduce criminal acts in adolescents. Conclusion. Some of the research results used as a source of literature review studies in pencak silat learning and pencak silat training provide new knowledge. Namely that pencak silat can be used as a means to instil character values, religious/spiritual, love for the country, manners for early childhood through pencak silat learning and adolescents through pencak silat training and its perguruan. The results of this study can be used as a theoretical basis that will be developed in the future so that it has greater meaning in building positive values towards early childhood and adolescence.